Understanding Livelihood Assets of Potato Farmer Household in Probolinggo Regency, East Java Province, Indonesia - Noor, Yumna Raisa; Hanani, Nuhfil; Fahriyah, Fahriyah (Agro Bali : Agricultural Journal, 2025)
Potato farming is critical in the local community of the mountainous terrain in Probolinggo Regency, East Java province. Despite the region's vulnerability to landslides and volcanic activity, its fertile land provides an optimal environment for agriculture, significantly contributing to potato production in Indonesia. However, farmers continue encountering challenges such as limited resources, market instability, and highland farming conditions. Understanding potato farmers' livelihood assets is crucial for supporting agricultural sustainability in the challenging terrain of Probolinggo Regency, East Java. This study used descriptive analysis, scoring, a Livelihood Index, and pentagon assets to characterize potato farmers' human, financial, physical, natural, and social assets. Results demonstrate the relative strength of financial assets, followed by natural, physical, human, and social assets, suggesting that farmers possess a moderate level of livelihood security.